(3CMcGe YbO GdJMcje h GLQGAGJg (B:s (3OQGSI ebGQfI (B/s - (3efOjd, GSYO aGVds ([(3Ohf ecGf(B]: s (3efThQGJ Rjf GdMbhbjI(B, s, 2011)
(3eaghe GJaGb GdJMcje h GdJCUjd GdJGQjNj dg h JejjRg Yf ZjQg h GdWHjYI GdbGfhfjI dg , fWGb GJaGb GdJMcje , TQhWg h CfhGYg , GNJjGQ GdeMcejf h JYjfge hhGLHGJ GdeMce h Mbhbg , JfMj GdeMce h YRdg h eSDhdjI GdeMce Yf CNWGFg , GdeHGOF GdCSGSjI ddeQGaYI CeGe GdeMcejf h GdCMhGd GdWGQFI Ydi gPg GdeQGaYI , cjajI EUOGQ bQGQ GdeMcejf h JfajP gPG GdbQGQ h GdWYf HgPg GdbQGQGJ (B.s
Keywords: (3GdELQGAGJ GdbGfhfjIs; (3GdJMcjes; (3GdYbhOs